Vancomycin removal during high-volume peritoneal dialysis in acute kidney injury patients - Ponce, Daniela [UNESP]; Zamoner, Welder [UNESP]; Freitas, Fernanda Moreira [UNESP]; Balbi, André [UNESP]; Awdishu, Linda (SAGE Publications, 2019)
Studies on vancomycin pharmacokinetics in acute kidney injury (AKI) patients on high-volume peritoneal dialysis (HVPD) are lacking. We studied the pharmacokinetics of intravenous (IV) vancomycin in AKI patients treated by HVPD who received a prescribed single IV dose of vancomycin (15 – 20 mg/kg total body weight) to determine the extent of vancomycin removal and to establish vancomycin dosing guidelines for the empirical treatment of AKI patients receiving HVPD. The application of 18 mg/kg vancomycin every 48 – 72 hours in AKI patients undergoing HVPD was required to maintain therapeutic concentrations.
Keywords: AKI; sepsis